Highly Ordered 3D Silicon Micro‐Mesh Structures Integrated with Nanowire Arrays: A Multifunctional Platform for Photodegradation, Photocurrent Generation, and Materials Conversion. Issue 1 (24th September 2018) - Chang, Bingdong; Tang, Yingying; Liang, Mingli; Jansen, Henri; Jensen, Flemming; Wang, Bo; Mølhave, Kristian; Hübner, Jörg; Sun, Hongyu
Abstract: Hierarchical three dimensional (3D) microstructures integrated with low‐dimensional nanomaterials can realize novel properties or improved performance. We report a unique conductive and highly ordered 3D silicon micro‐mesh structure, which is fabricated by standard lithography using a modified plasma etch process. Zinc oxide (ZnO) nanowires are then integrated with the micro‐mesh, and the density of ZnO nanowires (NWs) can be increased by around one order of magnitude compared with ZnO NWs on a 2D substrate. Owing to the high spatial density of ZnO NWs on the robust 3D silicon micro‐mesh structures, improved photocatalytic activity and stability can be achieved. A remarkable enhancement of photocurrent response is also observed. The ZnO can be converted into ZnS NWs and ZnO@ZIF‐8 as on the micromesh. This method is low‐cost and compatible with traditional complementary metal–oxide–semiconductor industries, and provides new possibilities for a wide range of devices based on micro‐nano‐electro‐mechanical and chemical systems. Abstract : Highly ordered 3D silicon micro‐mesh structures are used as a substrate for growth of different nanowire arrays. The density of nanowires is increased by one magnitude compared to the 2D substrates, which gives a significant improvement of photodegradation efficiency and photocurrent generation.